István Bethlen, el primer ministro de Hungría en España - Tari, Adrienn (Acta Hispanica, 2009)
There have been little to no investigations in Hungarian historiography concerning the visit of István Bethlen, Prime Minister of Hungary between 1921 and 1931, to Madrid. Unfortunately, the Hungarian National Archives only disposes of the text of the treaty drawn by the Hungarian-Spanish arbitrary committee. On the other hand, the Archive of the Spanish Ministry of Foreign Affairs holds numerous documents in relation with the treaty, amongst them, the correspondence between the heads of the ministries of foreign affairs. The Hungarian and Spanish press of the era also presents a detailed picture of the negotiations. Bethlen timed his Madrid visit to coincide with the congress of the League of Nations in the same city during the first days of June in 1929. The agenda of the congress contained two items that concerned Hungary, both related to the accords established in Trianon concerning the frontiers: the arrangement of the situation of double Romanian and Hungarian, and Serbian Hungarian nationality, respectively, and the question of minorities. After signing the treaty of the Hungarian-Spanish arbitrary committee, Bethlen also participated in the negotiations of the League of Nations. The aim of this paper is to analyze the reasons why Bethlen’s visit generated such an impact, mostly in the countries of the Little Entente, and to discuss the importance of the treaty drawn up by the Hungarian-Spanish arbitrary committee for Hungary, an important milestone also in the relations between the two countries.